Dynamic Information Acquisition, Comlementarity, and Market Liquidity - Zhifeng Cai (Rutgers University, Department of Economics, 2020)
This paper studies dynamic information acquisition in financial markets with information asymmetry. It first shows that multiplicity can arise in the information market due to a dynamic complementarity in information acquisition. It then characterizes interactions between information complementarity and market liquidity, in particular how market liquidity shapes information complimentarity through the liquidity component in future stock returns. I find that i)information complementarity is always more prominent in low-volatility financial market equilibrium; ii) information complementarity can be more prominent with less persistent stock fundamental and/or more persistent stock supply and iii) regardless of the type of financial market equilibrium, public disclosure always makes information complementarity less prominent.
Keywords: G1; G2; G3; 330; Information acquisition; Financial markets; Dynamic complementarity; Multiplicity; Market Liquidity